Sacred Iconographies in Chicana Cultural Productions - Román-Odio, Clara (Palgrave Macmillan, 2020)
This book examines the iconography of the Virgin of Guadalupe as a force for social justice and feminist emancipation within Chicana cultural productions from 1975-2010. In these productions the Virgin serves as a paradigm to unlock the histories of conquest and colonization, racism, and sexual oppression in the US-Mexico borderland and beyond...